DETERMINANTS OF FINANCIAL PERFORMANCE AMONG SAVINGS AND CREDIT CO-OPERATIVE SOCIETIES IN KAKAMEGA COUNTY KENYA - Esokomi, Emily; Mutua, Dr. Mbithi (International Journal of Finance and Accounting, 2018)
Purpose: The main objective of this study was to investigate determinants of financial performance of Savings and Credit Co-operative Societies in Kakamega County. Methodology: This study used a descriptive survey design. The target population for this study was 44 SACCOs in Kakamega County. The study used census sampling technique. Secondary data was obtained from Audited Annual Reports of the 44 SACCOs in Kakamega County- Kenya. The data was analyzed using the Statistical Packages for Social Sciences (SPSS). Analysis of the data collected focused on both the descriptive statistics (trends) and inferential statistics (Pearson Correlation Coefficients and multiple regression coefficients. The analyzed data was presented in frequency tables and graphs. Regression analysis was used to establish the relationship between the independent and dependent variables. Results: The study findings revealed that liquidity and return on equity were positively and significantly related, results further indicate that capital structure and return on equity were positively and significantly related. It was further established that assets quality was negatively and significantly related to return on equity. Similarly, results showed that income diversification was positively and significantly related to return on equity Policy recommendation: The study recommends that all SACCO's managers should be trained on the deployment of efficient systems to strengthen liquidity risk control fundamentals, that SACCOs should capitalize on efficient mobilization of members' savings and borrow less, unless they get cheap sources of external funds such as soft loans, that the Saccos should improve their investment assets levels and improve assets quality by reducing the rate of nonperforming loans through credit risk identification.